Polyvinyl and bismuth Nitrite based apron (PVABiN-Apron): fabrication and characterization - Bakri, Fahrul; Gareso, Paulus Lobo; Alomari, Ali Hamed; Heryanto, Heryanto; Ardiansyah, Ardiansyah; Syarifuddin, Syarifuddin; Abdul Karim, Muhammad Khalis; Taufiq, Ahmad; Tahir, Dahlang (Elsevier, 2025)
Developing PVA-based apron samples by incorporating varying concentrations of Bi(NO3)3 (10, 20, 30, and 40 wt%) through a mixing method has been studied. The identified chemical bonds from Fourier transform infrared (FTIR) are O-H, C-H, O=C=O, C=O, NO3−, and Bi-O-Bi. The crystallite size from the quantitative analysis of X-ray diffraction (XRD) shows an increase from 8.418 nm to 37.881 nm with increasing Bi(NO3)3 from 10 % to 40 %, respectively. We found that the best concentration is 40 wt% Bi(NO3)3, indicated by shielding performance's highest linear attenuation coefficient (LAC) of 17.398 cm−1, mass attenuation coefficient (MAC) of 9.719 cm2/g, and effective atomic number (Zeff) of 10.943 was evaluated at 80 kVp. Furthermore, this sample exhibited the lowest half-value layer (HVL) of 0.039 cm and the tenth-value layer (TVL) of 0.132 cm, indicating exceptional shielding efficiency. Regarding mechanical properties, the 30 wt% Bi samples achieved the highest tensile strength of 3.888 N/mm2 and elongation at a break of 18.445 %. These findings suggest that the 40 wt% Bi(NO3)3 apron sample offers a promising lead-free alternative for radiation protection, representing a crucial advancement in sustainable shielding materials. The practical implications of this research are significant, as it could lead to the development of more effective and environmentally friendly radiation protection materials.